A Review of Wear and Corrosion for Carbide-Coating on Different Method: HVOF Thermal Spray and Electrodeposition Method - Mazlan, Muhammad Zamir Zakwan; Kamdi, Zakiah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study is focused on the Carbide-coating with different types of method. The method involved in this study is between High Velocity Oxy-fuel (HVOF) thermal spray method and Electrodeposition method. In order to improve the material surface properties such as hardness, wear and corrosion, both methods are conducted. In this study, the substrate used is carbon steel and was placed at the cathode for electrodeposition process. AISI 1040 carbon steel also have been used as substrate for HVOF thermal spray carbide coating. The parameter for each method, for electrodeposition method used 50°C of Watts bath temperature and 0.5 A/cm² for current density, where for HVOF thermal spray is 45 LPM oxygen flowrate. The objective of this study is to compare the wear behavior, hardness and corrosion resistant of both carbide coating method. To compare the surface morphology, both methods have been analyzed using Scanning Electron Microscope no significant different shown on the surfaces. X-ray diffraction method were used to identify the phase analysis where both methods. Both methods have same element present but different in peak and amount of element. In wear testing, hardness testing and corrosion analysis, HVOF thermal spray samples gives better result compare to electrodeposited samples.